Diagnostic value of navigation-guided core needle biopsy in deep regions of the head and neck with focal FDG uptake on 18F-FDG PET/CT. Issue 5 (May 2020) - Gao, Ya; Wu, Wen-Jie; Zheng, Lei; Huang, Ming-Wei; Liu, Shu-Ming; Zhang, Jian-Guo
Abstract: Purpose: The aim of this study was to evaluate the feasibility and diagnostic accuracy of core needle biopsy (CNB) in patients with focal fluorodeoxyglucose (FDG) uptake on positron emission tomography/computed tomography (PET/CT) in deep regions of the head and neck, with the guidance of infrared navigation integrated with PET. Materials and methods: Patients with suspected primary or recurrent malignancies of the head and neck on PET/CT, from June 2016 to December 2018, were included. Before CNB, the region of interest was delineated and the ideal needle entry points, target sites, and a number of trajectories were designed on iPlan CMF 3.0. CNB was performed with the guidance of infrared navigation integrated with PET, according to the pre-plan. Sensitivity and diagnostic accuracy were analyzed by comparing the biopsy results with the final diagnosis. Results: Thirty-one consecutive patients were included. Among the 31 lesions, 18 were skull base, six were infratemporal fossa, and seven were maxillary region. The median values for SUVmax, SUVmean, and MTV were 6.09 (range: 1.43–24.67), 3.41 (range: 0.38–20.96), and 25.83 (range: 3.54–361.94) for the 31 lesions, respectively. Combined needle approaches were employed, including temporal (nine), subzygomatic (19), paramaxillary (11), and retromandibular (16) approaches. The depths of the 31 deep-region lesions, measured from the needle entry site on the skin to the target point, ranged from 1.33 cm to 7.82 cm (median 4.25 cm). There were three non-diagnostic lesions resulting from CNB, and these were all skull base. The diagnostic accuracy was 90.3%, while the sensitivity was 88%. According to the binary logistic regression for the final diagnosis, the only significant parameter was SUVmax. Conclusion: With the guidance of navigation integrated with PET, CNB is a feasible and accurate diagnostic modality, which is also an alternative to open biopsy in patients with suspected primary or recurrent malignancies in deep regions of the head and neck on PET/CT.